A literature review of the water services education and training needs of councillors in local authorities within the context of developmental local government agenda with special reference to Northern Cape Province - Tsibani, Fumene George (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil) -- University of Stellenbosch, 2004.